Dantrolene inhibits lysophosphatidylcholine-induced valve interstitial cell calcific nodule formation via blockade of the ryanodine receptor - Sylvester, Christopher B.; Amirkhosravi, Farshad; Bortoletto, Angelina S.; West, William J.; Connell, Jennifer P.; Grande-Allen, K. Jane (Frontiers in Cardiovascular Medicine, 2023)
Calcific aortic valve disease (CAVD), a fibrocalcific thickening of the aortic valve leaflets causing obstruction of the left ventricular outflow tract, affects nearly 10 million people worldwide. For those who reach end-stage CAVD, the only treatment is highly invasive valve replacement. The development of pharmaceutical treatments that can slow or reverse the progression in those affected by CAVD would greatly advance the treatment of this disease. The principal cell type responsible for the fibrocalcific thickening of the valve leaflets in CAVD is valvular interstitial cells (VICs). The cellular processes mediating this calcification are complex, but calcium second messenger signaling, regulated in part by the ryanodine receptor (RyR), has been shown to play a role in a number of other fibrocalcific diseases. We sought to determine if the blockade of calcium signaling in VICs could ameliorate calcification in an in vitro model. We previously found that VICs express RyR isotype 3 and that its modulation could prevent VIC calcific nodule formation in vitro. We sought to expand upon these results by further investigating the effects of calcium signaling blockade on VIC gene expression and behavior using dantrolene, an FDA-approved pan-RyR inhibitor. We found that dantrolene also prevented calcific nodule formation in VICs due to cholesterol-derived lysophosphatidylcholine (LPC). This protective effect corresponded with decreases in intracellular calcium flux, apoptosis, and ACTA2 expression but not reactive oxygen species formation caused by LPC. Interestingly, dantrolene increased the expression of the regulator genes RUNX2 and SOX9, indicating complex gene regulation changes. Further investigation via RNA sequencing revealed that dantrolene induced several cytoprotective genes that are likely also responsible for its attenuation of LPC-induced calcification. These results suggest that RyR3 is a viable therapeutic target for the treatment of CAVD. Further studies of the effects of RyR3 inhibition on CAVD are warranted.